Woman in CELAM and considerations about the female priesthood: balances and perspectives - Gutiérrez Velasco, Flavio (2017)
Firstly, it is discussed the position of the Latin American and Caribbean Bishops - through the General Assemblies from Medellín to Aparecida - on the role of women in the Church and in society, recognizing their rights and their equality with the male. Secondly, it presents the position of the Church about the female ministerial priesthood, and some reflections on this possibility, highlighting the proposal of a paradigm shift from that of the priesthood reserved for the male to that in which the woman also has access to it.